2012
DOI: 10.1107/s0108270112020367
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum tetrazinc, LaZn4

Abstract: The structure of lanthanum tetrazinc, LaZn(4), has been determined from single-crystal X-ray diffraction data for the first time, approximately 70 years after its discovery. The compound exhibits a new structure type in the space group Cmcm, with one La atom and two Zn atoms occupying sites with m2m symmetry, and one Zn atom occupying a site with 2.. symmetry. The structure is closely related to the BaAl(4), La(3)Al(11), BaNi(2)Si(2) and CaCu(5) structure types, which can be presented as close-packed arrangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…clusters. Earlier, we also observed that, in the binary phase LaZn 4 , the La atom was surrounded only by Zn atoms, forming an 18-vertex cluster (Oshchapovsky et al, 2012). The packing of the 16-vertex clusters and 18-vertex pseudo-Frank-Kasper polyhedra in the unit cell of both structures is shown in Fig.…”
Section: Commentmentioning
confidence: 51%
“…clusters. Earlier, we also observed that, in the binary phase LaZn 4 , the La atom was surrounded only by Zn atoms, forming an 18-vertex cluster (Oshchapovsky et al, 2012). The packing of the 16-vertex clusters and 18-vertex pseudo-Frank-Kasper polyhedra in the unit cell of both structures is shown in Fig.…”
Section: Commentmentioning
confidence: 51%
“…These states are mainly close to the lower valence band from –12 to –5 eV for Li 0.22 Zn 0.89 O in comparison to ZnO (from –7 to 0 eV). It should be noted that these oxides, like other zinc intermetallic phases earlier studied by us, get the greatest contribution to the density of states in the lower valence band from 3d‐type states of the zinc atoms 1317. Crystal orbital Hamilton population (COHP) and integrated COHP (iCOHP) calculations were used to obtain a quantitative evaluation of the bonding strength between the different types of atoms in both the ternary and the binary structures (see Figure 4, c–f, and Table 2).…”
Section: Resultsmentioning
confidence: 69%
“…The structure solution corresponds to the Cmcm space group and a model consistent with the structure type of PbSbO 2 Cl. The orthorhombic superstructure observed occurs in oxyhalides and is found rarely in intermetallics, e.g., in LaZn 4 [31] and SrPdGa 3 [35]. Similar to CeCuAl 3 a small Ag/Al mixing occurs on the Ag site along with a weak (ca.…”
Section: Crystal Structurementioning
confidence: 97%